Maintenance and Service Life Planning: process and interconnection - Azzalin, Maria (TECHNE - Journal of Technology for Architecture and Environment, 2020)
The horror pleni that Dorfles identifies with «Too much information, too many images, too many noises» is equivalent to the “Tzunami of information” that, according to Floridi, has invested the company in the last decade. Hypertrophy of the sign for the first, infosphere and onlife are the terms from which to start working on the second. A fourth revolution in which the expression onlife defines the new perimeter of our daily activities and ICT technologies, among these the IoT, increasingly configure the environment we live in and influence the processes related to maintaining quality in time and to life cycle assessment. It is not a new theme; the approaches brought about by digital transformation have been innovated. Equally worthy of challenge are the new problems and the new complexities related to interoperability and Big Data Analytics.